2022
DOI: 10.1080/2090598x.2022.2146859
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body granuloma development after calcium hydroxylapatite injection for stress urinary incontinence: A literature review and case report

Abstract: Objectives To present a case of foreign body granuloma (FBG) development after injection of calcium hydroxylapatite as a urethral bulking agent and to review all documented cases of this phenomenon in the literature. Methods We analyzed a new case of calcium hydroxylapatite-induced FBG. We also conducted a literature review of the PubMed, Embase, CINAHL, and Web of Science databases through March 2022. Reports were included if they contained stress urinary incontinence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…However, it has suggested that fillers might carry the potential risk of foreign body granuloma formation. The incidence rate of true granulomatous reactions to CaHA remains unknown, and published reports of such occurrences are rare [ 44 , 45 , 46 ]. Notably, among the included studies in the current systematic review, no granulomas, manifestations of allergy, ulcerations, or other serious adverse events were reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has suggested that fillers might carry the potential risk of foreign body granuloma formation. The incidence rate of true granulomatous reactions to CaHA remains unknown, and published reports of such occurrences are rare [ 44 , 45 , 46 ]. Notably, among the included studies in the current systematic review, no granulomas, manifestations of allergy, ulcerations, or other serious adverse events were reported.…”
Section: Discussionmentioning
confidence: 99%